Analysis of Postural Control in Patients Diagnosed with Unilateral Knee Osteoarthrosis and Its Relationship with the Risk of Falls - Robson Emiliano José de Freitas; Jaqueline Gleice Aparecida de Freitas; Carolina Pereira Vieira; Daniela Cristina Endres; Fábio Martins Inacio; Fernanda Grazielle da Silva Azevedo Nora (Advances in Orthopedics)
Introduction. Knee osteoarthrosis, whether subtle or marked, appears to alter the stability and performance of the knee joint in activities of daily living that prevent the maintenance of bipedal posture. However, there is still a gap in the literature as to how knee osteoarthritis can affect static balance. Objective. To analyze the performance of postural control in elderly diagnosed with unilateral knee osteoarthrosis. Materials and Methods. 40 elderly people of both sexes participated in this study, divided into two groups containing 20 elderly each. Group 1 (G1) consists of elderly patients who have received a diagnosis of unilateral knee osteoarthritis. Despite undergoing conservative treatment, their condition has shown insufficient improvement, leading to a clinical recommendation for total knee arthroplasty (TKA). The G2 group was made up of 20 elderly with an average age of 71.09 years, considered active, who do not have a diagnosis of osteoarthritis in the knee joint and practice physical activity. With the aid of a Baroscan pressure platform, the center of pressure (COP) displacement in the anteroposterior (COPAP) direction and mediolateral direction (COPML) and the area of center of pressure displacement were evaluated during bipedal postural control with eyes open and eyes closed. Results. During postural control with eyes open and eyes closed, the G1 group showed greater displacement of the COP in the anteroposterior direction—COPAP (p=0.007)—and mediolateral direction—COPML (p=0.033)—when compared to the G2 group. As for the area of displacement of the COP, group G1 presented a larger area of displacement (p=0.002) than group G2 during bipedal postural control with open eyes. For the condition with eyes closed, both groups showed similar behaviors, which resulted in no present statistically significant differences. Conclusion. The results suggest that unilateral knee osteoarthritis influences bipedal postural control and activities of daily living that require this static balance, since information from the somatosensory system is reduced, resulting in stability of tasks that require body control and promoting the risk of falls. From a clinical perspective, the results suggest that the assessment of bipedal postural control can assist orthopedic physicians in assessing joint stability in patients with unilateral knee osteoarthrosis.